2021
DOI: 10.2147/ijgm.s293400
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Seven-Year Follow-Up Outcomes of Percutaneous Endoscopic Lumbar Discectomy for Lumbar Degenerative Disease

Abstract: Purpose To investigate the long-term (> 7 years) clinical outcomes of percutaneous endoscopic lumbar discectomy for lumbar degenerative disease to address postoperative problems including postoperative dysesthesia (POD), residual back pain and segmental instability. Methods Inclusion and exclusion criteria were established. All patients who met the above criteria were treated by PELD using the transforaminal approach. Limited discectomy was performed to preserve the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Sang et al [8] reported that DH 10 years after TELD was 81.54 ± 17.40% of that before TELD, and there was no signi cant difference between the two. Li et al [4] reported that DH 7 years after TELD was 84.52 ± 5.66% of that before TELD, with no signi cant difference between the two. Our study found no signi cant difference in DH between the patients at the last follow-up and before the operation, which was consistent with the results of the above scholars.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Sang et al [8] reported that DH 10 years after TELD was 81.54 ± 17.40% of that before TELD, and there was no signi cant difference between the two. Li et al [4] reported that DH 7 years after TELD was 84.52 ± 5.66% of that before TELD, with no signi cant difference between the two. Our study found no signi cant difference in DH between the patients at the last follow-up and before the operation, which was consistent with the results of the above scholars.…”
Section: Discussionmentioning
confidence: 96%
“…is increasingly widely used in the treatment of lumbar degenerative diseases because of its advantages of less trauma, less bleeding and rapid recovery [1,4] . At present, there are many reports about the short-term e cacy of TELD [1,2,5−7] , but there are few reports on the medium-and long-term clinical evaluation of TELD for more than 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations